Socio-economic studies of coastal communities at the Fishing Port of Kutaraja, Banda Aceh, Indonesia. Issue 1 (February 2021) - Thaib, R; Ilda, I; Rahmah, A; Chaliluddin, M A; Aprilla, R M; Putra, D F; Fuadi, A
Abstract: Kutaraja Ocean Fishing Port (KOFP) has undergone significant development from small traditional-based fishing port (PPP, type C) to large modern-based fishing port (KOFP, type A) in the past couple years. The rapid development of the Kutaraja fishing Port has certainly had implications on socio-economic status of coastal communities around it. This study aimed to determine the socio-economic status of coastal communities around Kutaraja Ocean Fishing Port. Samples were taken from several respondents; fishermen (20 people), fish traders (15 people), food vendors (10 people) and management staff (2 people) to obtain primary data and secondary data. Data analysis was conducted descriptively with a quantitative approach i.e. the data collected was subsequently tabulated in the form of tables and graphs by using excel application. The results showed that the highest level of education of coastal communities around KOFP was high school level and the average ages of respondents was belong to the productive age at group of 27-50 years. Economic activity was seen from the number of dependents at most three people in each family and the rate of income averaged Rp.1.500.000-Rp. 2.000.000 per month. The pattern of public adaptation of social activity was demonstrated by the presence of some fish traders and food vendors who are still using the jetty area to perform their activities and cooperate with each other in utilizing the facilities. It can be concluded that the socio-economic status of coastal communities around KOFP was affected by activities in KOFP. The existence of KOFP showed a big impact on the socio-economic status of the coastal community around KOFP.